A core–shell structure QRu-PLGA-RES-DS NP nanocomposite with photothermal response-induced M2 macrophage polarization for rheumatoid arthritis therapy. Issue 39 (27th September 2019) - Chen, Xu; Zhu, Xufeng; Ma, Litao; Lin, Ange; Gong, Youcong; Yuan, Guanglong; Liu, Jie
Abstract : A novel therapeutic strategy for inducing macrophage M2 polarization by a core–shell QRu-PLGA-RES-DS NPs nanocomposite with photothermal response for RA therapy. Abstract : Rheumatoid arthritis (RA) is a degenerative joint disease caused by autoimmunity; for the effective treatment of RA while avoiding the side effects of conventional drugs, we have proposed a new therapeutic strategy to eliminate the inflammatory response in RA by regulating the immune system that promotes the transformation of M1-type macrophages to M2-type macrophages. Herein, we designed and synthesized a core–shell nanocomposite (QRu-PLGA-RES-DS NPs), which showed an effective therapeutic effect on RA by accurately inducing the polarization of M2 macrophages. In this system, the quadrilateral ruthenium nanoparticles (QRuNPs) with a photothermal effect were utilized as a core and the thermosensitive molecular poly (lactic- co -glycolic acid) (PLGA) modified with the targeted molecule dextran sulfate (DS) was employed as a shell. Then, the nanocarrier QRu-PLGA-DS NPs effectively improved the water solubility and targeting of resveratrol (RES) through self-assembly. Therefore, the QRu-PLGA-RES-DS NPs significantly enhanced the ability of RES to reverse the M1 type macrophages to the M2 type macrophages through an accurate release. In vivo experiments further demonstrated that the QRu-PLGA-RES-DS NPs could effectively accumulate in the lesion area with an exogenous stimulus, and this significantly enhanced the transformation of the M2 type macrophages and decreased the recruitment of the M1 type macrophages. Furthermore, the QRu-PLGA-RES-DS NPs effectively treated RA by eliminating the inflammatory response; in addition, photoacoustic imaging (PA) of the QRu NPs provided image guidance for the distribution and analysis of nanomedicine in inflammatory tissues. Hence, this therapeutic strategy promotes the biological applications of Ru-based nanoparticles in disease treatment.